115 Erroneously normal active B12 level in a case of subacute combined degeneration of the cord. (23rd August 2021) - Halliwell, Nicholas; Forsyth, Cecily; Taylor, Nicholas; Mangalasseril, Sarah; Sturm, Jonathan
Abstract : Objectives: Vitamin B12 is crucial for neurologic function, red blood cell production, and DNA synthesis. Deficiency can lead to a wide spectrum of haematologic and neuropsychiatric disorders including subacute combined degeneration of the cord. This report presents a case of a 47 y.o female who presented with subacute combined degeneration of the spinal cord with a normal active B12 level. Results: MRI demonstrated high T2 signal throughout the dorsal columns of the cervical and upper thoracic cord without enhancement consistent with subacute combined degeneration of the cord. Her blood count revealed a mild macrocytic anaemia. Total vitamin B12 was <80 pmol/L and active B12 was >128 pmol/L, confirmed on repeat testing. Functional vitamin B12 deficiency was confirmed by an elevated homocysteine level of 38.6 umol/L (reference range 4.4 to 13.6 umol/L) and elevated serum methylmalonic acid of 20.75 umol/L (reference range <0.32 umol/L). Intrinsic factor and gastric parietal cell antibodies were detected. Conclusion: Our patient had a clinical presentation consistent with B12 deficiency with an erroneously high active B12 level. Functional assays confirmed B12 deficiency, and a serological diagnosis of pernicious anaemia was made. This case illustrates the importance of not relying on any single test to exclude B12 deficiency.